2016
DOI: 10.1177/0963662515603272
|View full text |Cite
|
Sign up to set email alerts
|

From the preserves of the educated elite to virtually everywhere: A content analysis of Danish science news in 1999 and 2012

Abstract: In an attempt to qualify changes to science news reporting due to the impact of the Internet, we studied all science news articles published in Danish national newspapers in a November week in 1999 and 2012, respectively. We find the same amount of science coverage, about 4% of the total news production, in both years, although the tabloids produce more science news in 2012. Online science news also received high priority. Journalists in 2012 more often than in 1999 make reference to scientific journals and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In general journalism, more than half of all online news is copied from other media outlets or news agencies (Lund et al, 2009; Wurff and Lauf, 2005). Vestergaard and Nielsen (2015) confirmed this trend when they reported that only 58% of science news in 2012 was original. An increase in the use of foreign media sources was also found.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…In general journalism, more than half of all online news is copied from other media outlets or news agencies (Lund et al, 2009; Wurff and Lauf, 2005). Vestergaard and Nielsen (2015) confirmed this trend when they reported that only 58% of science news in 2012 was original. An increase in the use of foreign media sources was also found.…”
Section: Introductionmentioning
confidence: 76%
“…Bauer et al also documented a rise in science coverage, which has since been confirmed across countries: Italy (Bucchi and Mazzolini, 2003), Bulgaria (Bauer et al, 2006), Germany (Elmer et al, 2008) and by scholars in the United States (Clark and Illman, 2006; Pellechia, 1997). Surprisingly, however, the science coverage in Danish newspapers remained unchanged at 4% when comparing 1999 and 2012 (Vestergaard and Nielsen, 2015). Groves et al (2015) reached a similar result when they analysed Spanish online science news from 2002 to 2011.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding the visibility of the social sciences in the news coverage, differences by country are observable as well. While in Denmark the social sciences come in second in science coverage [Vestergård and Nielsen, 2017], they come in last in the U.K. [Vestergård and Nielsen, 2016] and are midrange in Croatia [Šuljok and Vuković, 2013]. While in Danish newspapers political triggers initiated coverage more often, scientific journals were an important trigger in the U.K. [Vestergård and Nielsen, 2017;Šuljok and Vuković, 2013].…”
Section: Social Science In the Mass Media Arenamentioning
confidence: 99%